Analysis of Tourist Preferences for Ecotourism Attractions in North Sumatera - Siregar, Onan Marakali; Selwendri, Selwendri (Research Horizon, 2024)
In Indonesia, ecotourism is an important part of the tourism industry where Indonesia is included in the list of the best ecotourism destinations in the world. The most important thing about ecotourism is efforts towards maintaining the preservation of the natural and cultural environment. This requires good and professional management of ecotourism attractions by the character of each tourist destination area. This research aims to group tourists based on psychographic segments towards ecotourism destinations in North Sumatra, determine the combination of product attributes at ecotourism destinations in North Sumatra that fulfill the desires of tourists per segment, and determine the preferences of tourists in each segment regarding their level. This research uses cluster and conjoint analysis methods which aim to group tourists into two groups based on tourism motivation, namely soft ecotourists and hard ecotourists along with the types of characteristics in each group. The analytical method used is a descriptive survey. Primary data was obtained from a questionnaire with a total of 120 respondents in 4 regions, namely Medan City, Langkat Regency, Karo Regency, and Toba Samosir Regency. The results of the research show that the average assessment of soft ecotourists shows that the comfort (accommodation) measure reaches the highest value, namely F-count accommodation = 81,656 and (p-value = 0.000), while hard ecotourists show the highest measure of commitment to environmental issues. On the other hand, the instruments that do not have differences between the two clusters are the commitment, duration, and interaction instruments.